2001
DOI: 10.1016/s0375-9601(01)00127-x
|View full text |Cite
|
Sign up to set email alerts
|

Nonextensive thermodynamic relations

Abstract: The generalized zeroth law of thermodynamics indicates that the physical temperature in nonextensive statistical mechanics is different from the inverse of the Lagrange multiplier, beta. This leads to modifications of some of thermodynamic relations for nonextensive systems. Here, taking the first law of thermodynamics and the Legendre transform structure as the basic premises, it is found that Clausius definition of the thermodynamic entropy has to be appropriately modified, and accordingly the thermodynamic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
213
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(226 citation statements)
references
References 11 publications
11
213
0
2
Order By: Relevance
“…But the average value will lose the distribution information about the inhomogeneous nature, and is unable to determine or mark the state of this system. Fortunately, we have confirmed that, for the nonextensive system like the self-gravitating one, the concept of temperature could generally split into two: the physical temperature related to the nonextensivity of the whole system [19], and the Lagrange temperature (the inverse of Lagrange multiplier) related to the local molecular collisions. The former is used to describe the 'equilibrium' state of the nonextensive system, and the latter is the measurable quantity in experiments.…”
Section: The Gravitational Temperaturementioning
confidence: 69%
See 3 more Smart Citations
“…But the average value will lose the distribution information about the inhomogeneous nature, and is unable to determine or mark the state of this system. Fortunately, we have confirmed that, for the nonextensive system like the self-gravitating one, the concept of temperature could generally split into two: the physical temperature related to the nonextensivity of the whole system [19], and the Lagrange temperature (the inverse of Lagrange multiplier) related to the local molecular collisions. The former is used to describe the 'equilibrium' state of the nonextensive system, and the latter is the measurable quantity in experiments.…”
Section: The Gravitational Temperaturementioning
confidence: 69%
“…One can find the condition (21) is satisfied naturally at the 'equilibrium' state. This expression is different from the physical temperature defined from the ensemble theory [19,20]. The gravitational temperature defined here is the molecular kinetics form of the physical temperature in the pure self-gravitational system and therefore is identical to physical temperature.…”
Section: The Gravitational Temperaturementioning
confidence: 93%
See 2 more Smart Citations
“…Raggio [10] had already shown that the equivalence between the first and third versions of Tsallis' formalism by utilizing the "q ↔ 1/q"-duality, i.e., maximizing S q under the energy constraint of U (3) q is equivalent to maximizing S 1/q under that of U (1) . Through the efforts [11,12] to generalize the zeroth law of thermodynamics within Tsallis' thermostatistics, it was revealed that the inverse temperature is not simply the Lagrange multiplier associated with the energy constraint. For this reason, the Tsallis variational problem and the Legendre transform structures have been extensively studied by e.g., so-called optimal Lagrange multiplier (OLM) formalism [13,14,15].…”
Section: Introductionmentioning
confidence: 99%